Effectiveness of the Lactation Buddy Intervention Based on WhatsApp Group on the Success of Exclusive Breastfeeding - Husnul Muthoharoh; Siti Sholikha; Kustini Kustini; Risma Syahadatut Dinuriyah; Hibatun Mubarokah El Fitri (Jurnal Kebidanan Midwiferia, 2025)
Exclusive breastfeeding is the most effective nutritional intervention to prevent stunting. However, Lamongan Regency still records low exclusive breastfeeding coverage. This study aimed to analyze the effectiveness of the Lactation Buddy intervention through WhatsApp Group in supporting exclusive breastfeeding practice. This research employed a quasi-experimental design with a non-randomized control group pretest-posttest. The study was conducted in Deket Kulon Village, Deket Sub-district, Lamongan Regency, involving 60 mothers with infants aged 0–6 months who were recruited using purposive sampling and divided into intervention (n=30) and control (n=30) groups. The intervention group received three-month assistance through WhatsApp Group facilitated by health workers and lactation counselors, while the control group obtained standard care. Data were collected using structured questionnaires, interviews, and observations. Results indicated significant improvement in the intervention group: the average knowledge score increased from 65.3 to 85.7 (p<0.001), positive attitudes toward breastfeeding rose from 60% to 80% (p=0.002), and correct breastfeeding practices improved from 53.3% to 83.3% (p<0.001). Furthermore, exclusive breastfeeding success was achieved by 83.3% of mothers in the intervention group compared to 56.7% in the control group (p=0.01). The findings confirm that the Lactation Buddy intervention via WhatsApp Group is effective in improving maternal knowledge, attitudes, practices, and exclusive breastfeeding success, and may serve as a scalable strategy to support stunting prevention in Deket Kulon Village, Deket Sub-district, Lamongan Regency.